Role of Artificial Intelligence in Information Security: Challenges and Future Directions - Manish L Jivtode, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The rapid growth of digital data, cloud computing, and social media platforms has led to a significant increase in cyber threats, making information security a major global challenge. Traditional security methods often fail to detect complex, dynamic, and large-scale cyber -attacks in real time. In this context, Artificial Intelligence (AI) has emerged as a transformative approach to enhancing information security systems by enabling intelligent, automated, and more adaptive defense systems. This paper examines how AI is used in information security, specifically focusing on its ability to improve threat detection, malware analysis, and data protection. AI technologies such as machine learning, deep learning, and data mining, are highly effective at identifying patterns, and spotting unusual activities. Unlike old rule-based methods, AI can predict potential security breaches with higher accuracy and speed, providing a more robust shield against hackers. However, using AI security also brings certain challenges. These include concerns regarding data privacy concerns, lack of transparency in in how AI makes decisions, and the risk of criminal using AI for more advanced attacks. Furthermore, the high cost of the technology and ethical questions about automated surveillance are significant obstacles. The conclusion of this paper is that, although AI has the potential to transform cybersecurity, greater emphasis must be placed on developing more transparent and ethical AI models.These technical and regulatory challenges must be addressed to create a secure and trustworthy digital future.
Keywords: Artificial Intelligence; Information Security; Cyber Security; Machine Learning; Threat Detection; Encryption; Adversarial Attacks; Explainable AI